Virtual patients in continuing medical education and residency training: a pilot project for acceptance analysis in the framework of a residency revision course in pediatrics = Virtuelle Patienten in der ärztlichen Fort- und Weiterbildung : ein Pilotprojekt zur Akzeptanzanalyse im Rahmen eines Weiterbildungs-Repetitoriums in der Pädiatrie - Lehmann, Ronny; Hanebeck, Benjamin; Oberle, Stephan; Simon, Anke; Choukair, Daniela; Tönshoff, Burkhard; Huwendiek, Sören (GMS Zeitschrift für medizinische Ausbildung, 2015)
Virtual patients (VPs) are a one-of-a-kind e-learning resource, fostering clinical reasoning skills through clinical case examples. The combination with face-to-face teaching is important for their successful integration, which is referred to as “blended learning”. So far little is known about the use of VPs in the field of continuing medical education and residency training. The pilot study presented here inquired the application of VPs in the framework of a pediatric residency revision course.
Im PDF erscheint der Artikel auf den Seiten 1 - 4 in englischer Sprache und auf den Seiten 5 - 9 in deutscher Sprache
Gesehen am 17.06.2020